An Overview of the Synthesis of Biologically Active Cyclodepsipeptides. Issue 1 (7th January 2022) - Farah, Harra Ismi; Supratman, Unang; Hidayat, Ace Tatang; Maharani, Rani
Abstract: Cyclodepsipeptide are a class of natural cyclic peptides that have a wide range of biological activities, hence the potential to be developed as new drug candidates. Cyclodpesipeptides comprise a backbone of amide bonds and at least one ester moiety, thus are complex and challenging to synthesis. Generally, cyclodepsipeptides are synthesised via solid‐phase peptide synthesis, solution‐phase or a combination of solid and solution‐phase. Currently, solid‐phase peptide synthesis is more in demand, but it also has several challenges in its application especially for the cyclodepsipeptide that contains N ‐methylated residues, as well as solution‐phase peptide synthesis tends to have a longer reaction step. Therefore, the combination of solid and solution‐phase peptide synthesis is a better alternative. This review discusses the synthetic strategies for cyclodepsipeptides including the preparation of precursor and macrocyclization. Abstract : Cyclodepsipeptide is a cyclic peptide group that has one or more ester bonds; therefore, the synthesis strategy approach begins by preparing a hydroxy acid precursor followed by linear depsipeptide formation, including the formation of ester bonds in the peptide framework and the last step is macrocyclization either through solid phase or solution peptide synthesis strategies.